Changes in treatment and mortality of acute myocardial infarction in Estonian tertiary and secondary care hospitals in 2001 and 2007 - Blöndal Mai; Ainla Tiia; Marandi Toomas; Baburin Aleksei; Eha Jaan (BMC Research Notes, 2012)
Abstract Background High quality care for acute myocardial infarction (AMI) improves patient outcomes. Still, AMI patients are treated in hospitals with unequal access to percutaneous coronary intervention. The study compares changes in treatment and 30-day and 3-year mortality of AMI patients hospitalized into tertiary and secondary care hospitals in Estonia in 2001 and 2007. Results Final analysis included 423 cases in 2001 (210 from tertiary and 213 from secondary care hospitals) and 687 cases in 2007 (327 from tertiary and 360 from secondary care hospitals). The study sample in 2007 was older and had twice more often diabetes mellitus. The patients in the tertiary care hospitals underwent reperfusion for ST-elevation myocardial infarction, cardiac catheterization and revascularisation up to twice as often in 2007 as in 2001. In the secondary care, patient transfer for further invasive treatment into tertiary care hospitals increased (P < 0.001). Prescription rates of evidence-based medications for in-hospital and for outpatient use were higher in 2007 in both types of hospitals. However, better treatment did not improve significantly the short- and long-term mortality within a hospital type in crude and baseline-adjusted analysis. Still, in 2007 a mortality gap between the two hospital types was observed (P < 0.010). Conclusions AMI treatment improved in both types of hospitals, while the improvement was more pronounced in tertiary care. Still, better treatment did not result in a significantly lower mortality. Higher age and cardiovascular risk are posing a challenge for AMI treatment.